Determinants of blood pressure in preschool children - Simonetti, Giacomo D.; Schwertz, Rainer; Klett, Martin; Hoffmann, Georg F.; Schaefer, Franz; Wühl, Elke (Circulation, 2011)
Hypertension is the leading risk factor for cardiovascular disease. Although accumulating evidence suggests tracking of blood pressure from childhood into adult life, there is little information regarding the relative contributions of genetic, prenatal, biological, behavioral, environmental, and social determinants to childhood blood pressure.